Managing clinic variability with same-day scheduling, intervention for no-shows, and seasonal capacity adjustments - YANG, Kum Khiong (Institutional Knowledge at Singapore Management University, 2020)
This study investigates demand and capacity strategiesfor managing clinic variability. These include (i) same-day scheduling tocontrol random walk-ins, (ii) no-show intervention, where the clinic callsadvance-booked patients a day before to identify and release canceled slots tosame-day patients, and (iii) adjustments to daily number of appointments foradvance-booked patients to match seasonal variations in same-day demand. Thesestrategies are tested over the individual-block/fixed-interval (IBFI) and theDome appointment rules. The resulting appointment systems are tested underscenarios with different levels of same-day demand, demand seasonality,no-shows and cost ratios. The goal is to minimize the weighted sum of patients’wait time and physician’s idle-time and overtime. Our results show that choosingthe appropriate refinements in the order of appointment rules, same-day scheduling,no-show intervention, and capacity adjustment provides maximum improvement. The total costbenefit of demand strategies (i) and (ii) is 7 to 21%, whereas the benefit ofcapacity strategy (iii) is as high as 6%. Analysis is provided on the main and interactioneffects of different environmental factors on the demand and capacitystrategies. Our study affirms the universality of the Dome rule to perform wellwhen combined with demand and capacity strategies across differentenvironments.